2020
DOI: 10.1177/0218492320970018
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter experience: early outcome of mitral valve repair in patients with ischemic mitral regurgitation

Abstract: Background Ischemic mitral regurgitation is associated with poor outcomes. The optimal surgical strategy for management of ischemic mitral regurgitation is still debated. The objective of this study was to evaluate the early mortality and morbidity of mitral valve repair in patients with ischemic mitral regurgitation undergoing coronary artery bypass grafting. Methods We performed a retrospective, observational, cohort study on prospectively collected data on 136 consecutive coronary artery bypass graft patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…An increasing number of studies have reported that coronary artery bypass grafting (CABG) plus simultaneous mitral valve repair could be an effective surgical plan for moderate IMR, although recurrent MR may occur. Surgery eliminates MR immediately following the operation, reverses LV remodeling, ameliorates LV performance, and allows a more reliable repair of moderate IMR [ 10 , 11 , 12 ]. The results of our previous study showed that concomitant mitral valve repair may improve New York Heart Association (NYHA) functional class and reduce residual MR, with no increase in surgical mortality, morbidity, or follow-up deaths [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have reported that coronary artery bypass grafting (CABG) plus simultaneous mitral valve repair could be an effective surgical plan for moderate IMR, although recurrent MR may occur. Surgery eliminates MR immediately following the operation, reverses LV remodeling, ameliorates LV performance, and allows a more reliable repair of moderate IMR [ 10 , 11 , 12 ]. The results of our previous study showed that concomitant mitral valve repair may improve New York Heart Association (NYHA) functional class and reduce residual MR, with no increase in surgical mortality, morbidity, or follow-up deaths [ 13 ].…”
Section: Introductionmentioning
confidence: 99%